Composite artefacts in the Ancient Near East : exhibiting an imaginative materiality, showing a genealogical nature - Di Paolo, Silvana (Archaeopress ancient Near Eastern archaeology ;, 2018)
This volume represents a first attempt to conceptualise the construction and use of composite artefacts in the Ancient Near East by looking at the complex relationships between environments, materials, societies and materiality.